Integrated Home‐ and Community‐Based Services Improve Community Survival Among Independence at Home Medicare Beneficiaries Without Increasing Medicaid Costs. Issue 7 (10th May 2019) - Valluru, Girish; Yudin, Jean; Patterson, Christine L.; Kubisiak, Joanna; Boling, Peter; Taler, George; De Jonge, Karl Eric; Touzell, Steve; Danish, Ann; Ornstein, Katherine; Kinosian, Bruce
Abstract : OBJECTIVES: To determine the effect of home‐based primary care (HBPC) for frail older adults, operating under Independence at Home (IAH) incentive alignment on long‐term institutionalization (LTI). DESIGN: Case‐cohort study using HBPC site, Medicare administrative data, and National Health and Aging Trends Study (NHATS) benchmarks. SETTING: Three IAH‐participating HBPC sites in Philadelphia, PA, Richmond, VA, and Washington, DC. PARTICIPANTS: HBPC integrated with long‐term services and supports (LTSS) cases (n = 721) and concurrent comparison groups (HBPC not integrated with LTSS: n = 82; no HBPC: n = 573). Cases were eligible if enrolled at one of the three HBPC sites from 2012 to 2015. Independence at Home‐qualified (IAH‐Q) concurrent comparison groups were selected from Philadelphia, PA; Richmond, VA; and Washington, DC. INTERVENTION: HBPC integrated with LTSS under IAH demonstration incentives. MEASUREMENTS: Measurements include LTI rate and mortality rates, community survival, and LTSS costs. RESULTS: The LTI rate in the three HBPC programs (8%) was less than that of both concurrent comparison groups (IAH‐Q beneficiaries not receiving HBPC, 16%; patients receiving HBPC but not in the IAH demonstration practices, 18%). LTI for patients at each HBPC site declined over the three study years (9.9%, 9.4%, and 4.9%, respectively). Costs of home‐ and community‐based services (HCBS) were nonsignificantly lower among integrated care patients ($2151/mo; observed‐to‐expected ratio = .88 [.68‐1.09]). LTI‐free survival in the IAH HBPC group was 85% at 36 months, extending average community residence by 12.8 months compared with IAH‐q participants in NHATS. CONCLUSION: HBPC integrated with long‐term support services delays LTI in frail, medically complex Medicare beneficiaries without increasing HCBS costs. Abstract : See related editorial byLeff et al .